Critically ill patients with COVID-19 show lung fungal dysbiosis with reduced microbial diversity in patients colonized with Candida spp. (April 2022) - Viciani, Elisa; Gaibani, Paolo; Castagnetti, Andrea; Liberatore, Andrea; Bartoletti, Michele; Viale, Pierluigi; Lazzarotto, Tiziana; Ambretti, Simone; Lewis, Russell; Cricca, Monica
Highlights: Candida spp. colonization was higher in patients with COVID-19 than in those without COVID-19. ARDS in COVID-19 was characterized by lung dysbiosis and decreased fungal diversity. Ascomycota was more represented in patients with COVID-19 not colonized with Candida spp. ABSTRACT: Background: The COVID-19 pandemic has intensified interest in how the infection affects the lung microbiome of critically ill patients and how it contributes to acute respiratory distress syndrome (ARDS). We aimed to characterize the lower respiratory tract mycobiome of critically ill patients with COVID-19 in comparison to patients without COVID-19. Methods: We performed an internal transcribed spacer 2 (ITS2) profiling with the Illumina MiSeq platform on 26 respiratory specimens from patients with COVID-19 as well as from 26 patients with non–COVID-19 pneumonia. Results: Patients with COVID-19 were more likely to be colonized with Candida spp. ARDS was associated with lung dysbiosis characterized by a shift to Candida species colonization and a decrease of fungal diversity. We also observed higher bacterial phylogenetic distance among taxa in colonized patients with COVID-19. In patients with COVID-19 not colonized with Candida spp., ITS2 amplicon sequencing revealed an increase of Ascomycota unassigned spp. and 1 Aspergillus spp . –positive specimen. In addition, we found that corticosteroid therapy was frequently associated with positive Galactomannan cell wall component of Aspergillus spp. among patients with COVID-19. Conclusion: Our study underpins that ARDS in patients with COVID-19 is associated with lung dysbiosis and that an increased density of Ascomycota unassigned spp. is present in patients not colonized with Candida spp.